Penerapan Metode Segitiga Restitusi untuk Mengembangkan Civic Sense Peserta Didik di Kelas VIII Sekolah Menengah Pertama - Amalia Silmi Hunafa; Azah Siti Nurazizah; Ade Usman; Jamilah; Tetep; Asep Rusmayadi (PTK: Jurnal Tindakan Kelas, 2025)
Problems related to low positive student discipline, characterized by tardiness, asking for permission to leave the classroom, and a lack of concern for classroom cleanliness. This study aims to assess the extent to which the Triangle of Restitution method fosters Civic Sense in the aspects of discipline and responsibility in students in class VIII B of SMPN 5 Garut. The method used in this study was Classroom Action Research (CAR), utilizing Kurt Lewin's cycle model consisting of four stages: planning, implementation, observation, and reflection. The subjects consisted of teachers and students, while the object of the research was the sense of citizenship in the aspects of discipline and responsibility of students. Data were collected through observation, interviews, and documentation. Data analysis was conducted using interactive analysis techniques, including data presentation and drawing conclusions. The results showed that the implementation of the Triangle of Restitution method had a significant positive impact on the growth of Civic Sense in class VIII B students. This improvement was evident in the progress in each cycle, with an average final percentage reaching 77% in the second cycle, meeting the specified target. Based on these results, it can be concluded that the Triangle of Restitution method has proven effective in fostering Civic Sense in students.